2015
DOI: 10.1097/olq.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection Among 2460 Men in Denmark

Abstract: Human papillomavirus is highly prevalent in the general male population of Denmark, with HPV-16 and HPV-51 being the most prevalent. Polymerase chain reaction detects twice as many positive samples as HC2 but includes HPVX, possibly representing cutaneous HPV types found on normal genital skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…In addition, the Denmark study showed the highest HPV infection prevalence among men aged 20 to 29 years in contrast to our study, which demonstrated a lower prevalence among younger groups, with a higher and persistent prevalence among older age groups. It may be that the cumulative prevalence of persistent infections would be expected to increase with age, as was shown in oral HPV infection .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, the Denmark study showed the highest HPV infection prevalence among men aged 20 to 29 years in contrast to our study, which demonstrated a lower prevalence among younger groups, with a higher and persistent prevalence among older age groups. It may be that the cumulative prevalence of persistent infections would be expected to increase with age, as was shown in oral HPV infection .…”
Section: Discussioncontrasting
confidence: 99%
“…This pattern of infection is similar to the prevalence of oral HPV infection from the NHANES 2009-2010 previously reported . The overall HPV prevalence is similar to recent research from Denmark, which reported a 41.8% overall HPV prevalence, with the same high-risk HPV subtype 51 as the most prevalent . In female individuals, the most prevalent HPV subtype was 53, and subtype 51 was the fourth most common .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Details on this cross-sectional study have been described previously. 32 Briefly, male personnel at a number of military barracks in Denmark were invited to participate in the study. All men received approximately €25 for their participation and gave their informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…For Denmark, publicly-available prevalence estimates were available for HCV 39 and HIV 38 . For EBV 36 and HPV 42 , we used published seroprevalence and qPCR positivity estimates, respectively, as proxies for overall prevalence. When in-country estimates weren't available, we resorted to the best data source from a country or region with similar demographics, such as Switzerland (BKV) 45 , the Netherlands (MCV, CMV) 34,47 , Northern Europe (AAV-2) 43 , or Germany (HSV-1) 32 .…”
Section: Discussionmentioning
confidence: 99%